2016
DOI: 10.1103/physrevc.93.054616
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent Hartree-Fock calculations for multinucleon transfer and quasifission processes in theNi64+U238reaction

Abstract: Background: Multinucleon transfer (MNT) and quasifission (QF) processes are dominant processes in lowenergy collisions of two heavy nuclei. They are expected to be useful to produce neutron-rich unstable nuclei. Nuclear dynamics leading to these processes depends sensitively on nuclear properties such as deformation and shell structure.Purpose: We elucidate reaction mechanisms of MNT and QF processes involving heavy deformed nuclei, making detailed comparisons between microscopic time-dependent Hartree-Fock (T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 145 publications
(477 reference statements)
6
124
0
Order By: Relevance
“…, TKE) and impact parameter b, and to examine the origin of the wide mass ratio component, microscopic approaches TDHF and TDRPA have been used. TDHF is a mean-field approach incorporating onebody dissipation that has previously been used to explore dynamical reaction processes such as quasifission [10,[24][25][26][27][28][29][30]. In this work, a 3D TDHF code [31,32], employing the SLy4d parametrization [33] of the Skyrme energydensity functional [34] has been used to explore reaction outcomes for 58,60 Ni+ 60 Ni at the three representative energies shown in Fig.…”
Section: Thementioning
confidence: 99%
“…, TKE) and impact parameter b, and to examine the origin of the wide mass ratio component, microscopic approaches TDHF and TDRPA have been used. TDHF is a mean-field approach incorporating onebody dissipation that has previously been used to explore dynamical reaction processes such as quasifission [10,[24][25][26][27][28][29][30]. In this work, a 3D TDHF code [31,32], employing the SLy4d parametrization [33] of the Skyrme energydensity functional [34] has been used to explore reaction outcomes for 58,60 Ni+ 60 Ni at the three representative energies shown in Fig.…”
Section: Thementioning
confidence: 99%
“…Recent investigations have also shown that the one-body dissipation mechanisms included in TDHF were the most relevant to describe fully damped reactions such as quasi-fission [55][56][57][58][59][60]. In this manuscript we study various aspects of deep-inelastic collisions using the TDHF approach.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to compute the probability to form a fragment with a given number of nucleons [27][28][29][30][31][32], but the resulting fragment mass and charge distributions are often underestimated in dissipative collisions [33,34]. Much effort has been done to improve the standard mean-field approximation by incorporating the fluctuation mechanism into the description.…”
Section: Introductionmentioning
confidence: 99%
“…A number of models was developed for a description of the reaction mechanism in the multi-nucleon transfer process in quasi-fission reactions [1][2][3][4]. Within the last few years the time-dependent Hartree-Fock (TDHF) approach [5][6][7] has been utilized for studying the dynamics of quasifission [7][8][9][10][11][12][13][14][15][16][17] and scission dynamics [18][19][20][21][22][23]. Such calculations are now numerically feasible to perform on a 3D Cartesian grid without any symmetry restrictions and with much more accurate numerical methods [24][25][26].…”
Section: Introductionmentioning
confidence: 99%